Optimizing Hydrophilicity in NiO/Graphene Composites Via Stearic Acid Treatment for Humidity-to-Energy Applications - Mohamed Mustakim, Nurul Syafiqah; Dayana Kamaruzaman; Bin A Subki, A Shamsul Rahimi; Mohd Hanapiah Abdullah; Mohd Firdaus Malek; Norfarariyanti Parimon; Mohd Khairul Ahmad; Suriani Abu Bakar; Nagamalai Vasimalai; Mamat, Mohamad Hafiz (International Journal of Integrated Engineering, 2024)
Converting water molecules into energy, this research field has garnered significant attention, yet it is still in its early stages of exploration. The main challenge in humidity-to-energy development is the effectiveness of material in water absorption. This article presents a study on surface modification through stearic acid treatment aimed at optimizing the hydrophilicity of hygroscopic material, thereby improving humidity energy harvesting performance. Here, we successfully synthesized a novel NiO/Graphene on cellulose substrate (NiO/Gr/cellulose) as the hygroscopic material using the sonicated solution immersion method. A humidity-to-energy device was fabricated by utilizing the NiO/Gr/cellulose, yielding an output voltage of 2.26 mV, a current density of 0.18 nA/cm², and a power output of 0.51 pW at 75% relative humidity. This research highlights the potential of NiO/Gr/cellulose with sufficient hydrophilicity as a promising hygroscopic material, offering significant future prospects in humidity energy harvesting technology.